The impact of a home visiting program on the care environment of Brazilian adolescent mothers - an descriptive exploratory study - Silva, Letícia Aparecida da; Siqueira, Luciola Demery; Oliveira, Larayne Gallo Farias; Miguel Filho, Euripedes Constantino; Polanczyk, Guilherme Vanoni; Fracolli, Lislaine Aparecida (Frontiers in Global Women's Health, 2025)
BackgroundThere is evidence of a link between the environment and child development (CD) in early childhood, justifying the importance of studying the characteristics of the environment in order to understand it and thus intervene in CD.ObjectivesTo describe the changes in the environment of families who participated in the Young Caring Mothers Programme (YCMP).MethodThis is an exploratory, descriptive study focusing on the home environment of adolescent mothers and their babies supported by the YCMP, derived from the randomised controlled clinical trial “The effect of the Young Pregnant Women Visitation Program on child development: a pilot study” (registered at clinicaltrial.gov; identifier: NCT02807818).Sample80 pregnant adolescents, 40 in the intervention group (IG) and 40 in the control group (CG).InstrumentIT-HOME inventory.ResultsAt 6 and 12 months, both groups showed a tendency for the median to increase, although this increase was more pronounced in the IG. From 12 to 24 months, both groups showed a tendency for the median to decrease, with a more marked decrease in the CG, which reached values lower than those previously observed. No significant differences were found between the groups in the overall IT-HOME scores, but it was found that the relationship between maternal schooling and the score on the subscales emotional and verbal responsibility of the caregiver was greater in the control group (4. 5 points more) in mothers with less schooling (primary school) than in mothers with the same schooling in the control group (p = 0.02), this satisfactory result was obtained in the 6 and 24 month measurements, in the latter the intervention group scored 3 points higher than the control group (p = 0.05).DiscussionThe results show a small impact of the YCMP on the quality of the “environment” of the families supported, but the impact is on a dimension of the environment that is very important for child development: responsive relationships of the mother with low schooling and high vulnerability.ConclusionsThe YCMP can have an impact on the care environment of children under 3 years of age in families with high social vulnerability.